Research on Passivity Based Controller of Three Phase Voltage Source PWM Rectifier - Wang Jiuhe; Wang Mian; Zhang Li; Yin Hongren (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Euler-Lagrange (EL) model of voltage source PWM rectifier is set up based on its model in synchronous dq coordinates. Passivity based controller is designed on the basis of passivity and EL model of voltage source PWM rectifier. Three switching function are educed by passivity based controller. A switching function is only realized in engineering consequently. Voltage source PWM rectifier using passivity based controller has many advantages, such as simpler structure, low total harmonic distortion, and good disturbance rejection performance. Passivity based control law is proved feasible by simulink simulation. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1343